Re-evaluating the evidence of aflatoxin B1 intercalation into smectite interlayer: a review based on basal spacing data - Widyawanto Prastistho; Cintya Nurul Apsari; Niar Gusnaniar; Wawan Budianta; Michael Angelo B. Promentilla; Setyowati Triastuti Utami (Universitas Sebelas Maret, 2025)
The bonding mechanism of aflatoxin B1 (AfB1) onto smectite in the batch adsorption test remains a subject of ongoing debate. One key aspect under contention is whether the interlayer of smectite is accessible to the AfB1 molecule. Some researchers contested the possibility of AfB1 intercalation into the smectite interlayer by highlighting the lack of discernible differences in basal spacing value before and after the adsorption experiment. Conversely, others have advanced the opposite argument based on observations indicating an increase in basal spacing value after adsorption. This study aims to resolve the discrepancy through a comparative examination of data from several previous studies that reported basal spacing values derived from X-ray diffraction (XRD) analysis, both before and after adsorption tests. By also considering the characteristic swelling behavior of smectite, this comparative examination explains the differing perspectives. The lack of discernible differences in basal spacing value pre- and post-adsorption tests, which was interpreted as the absence of AfB1 intercalation, was attributed to the fact that the initial samples were inherently in hydrated condition, as indicated by basal spacing values of 1.41 to 1.59 nm, whereas in the dry state, these values would typically be 0.98 to 1.0 nm, thereby precluding further expansion. Consistent with a previous study that suggested AfB1 bonding to smectite in hydrated conditions occurred through hydrogen bonding within the interlayer, we propose that the hydration state of smectite will significantly influence AfB1 uptake. Thus, further research of adsorption test to investigate the relationship between AfB1 uptake as a function of the hydration state on smectite minerals is strongly suggested.